Evaluación de la obtención de polihidroxialcanoatos (PHAs) partiendo del residuo de almidón de papa por medio de Bacillus subtilis a nivel laboratorio (2017)
The present work evaluates the preparation of polyhydroxyalkanoates (PHAs) from the residue of potato starch; This residue came from the production processes of potato in phosphorus, carried out in the company Comercializadora Nacional de Papas R & G. Initially the conditioning of the starch is carried out for the fermentation process and the conditioning of the microorganism Bacillus subtilis used as accumulator of the biopolymer. This work is carried out at the “Nodo Tecnoparque Sena Bogotá” and at the “Centro de Gestion Industrial Sena, sede Paloquemao Bogotá”